DISTRBUTION OF SEAGRASS SPESCIES BASED ON SUBSTRATE TYPE IN THE WATERS OF SAWAPUDO VILLAGE, KONAWE REGENCY - Suhartin, Suhartin; Nur, Andi Irwan; Ira, Ira; Lestari, Rizky Ayu (Jurnal Perikanan Unram, 2025)
Seagrass meadows, which are extensive and distributed across various substrate types, play a crucial role in nutrient management and maintaining aquatic ecosystem stability. This study aims to determine the distribution of seagrass species, including seagrass density and seagrass cover percentage based on substrate types in the waters of Sawapudo Village. The purpose is to describe the condition of seagrass ecosystem distribution and provide initial information for coastal and marine resources. Seagrass sampling was conducted using quadrat transects at three stations determined by substrate type. The substrate types were sandy-muddy at Station I, muddy at Station II, and sandy at Station III. During the study period, the seagrass species found at the three stations were Enhalus acoroides, Thallasia hemprichii, Cymodocea rotundata, and Halodule uninervis. The average seagrass density at Station I was 216 shoots/m², at Station II was 293 shoots/m², and at Station III was 191 shoots/m². The seagrass cover percentage at Station I was 67.97%, at Station II was 72.45%, and at Station III was 53.44%. The seagrass distribution pattern at Station I had an Index of 1.64, at Station II an Index of 1.61, and at Station III an Index of 1.15. Differences in seagrass density are attributed to variations in substrate types. The seagrass cover percentage is influenced by the number of shoots, morphology, and substrate type. The seagrass species distribution pattern at the research location is clumped. Key words: Coverage, Density, Distribution Pattern, Seagrass, Substrate Type